HEARING LOSS: ATTENDANCE ACROSS MULTICENTRES, WHERE IS IT HEADING? - Sarah Jane Messeder MBChB, BSc Timo Stoever PhD, MD., Uwe Baumann PhD, Dipl.-Ing, Lisa Caulley MD, MPH., Jasenka Broz Frajtag, Forbes Lauder BSc. & Alison Kennedy BSc Georgios Kontorinis FRCS (ORL), MD, MSc. (International Journal of Research Science and Management, 2017)
Objective To determine the trends of hearing loss by using data from different tertiary centres across Europe and Canada. Methods The number of attendances from April 2012 until April 2015 to the Departments of Audiology in four different tertiary centres located in Canada, Croatia, Germany and the UK were collected retrospectively. Additionally, where available, similar data from 10 years ago were collected. Results A significant upward trend in attendances was seen in the German and Croatian centres over the last decade whilst the Canadian centre demonstrated a decline. In all countries, the number of attendances have plateaued. Within the UK centre, the annual cost of hearing aids exceeds £1.5 million for a catchment area of 1.16 million people. Conclusions These trends may represent the earlier detection of hearing loss, increased societal awareness and improvements in safety to reduce work-induced noise pollution..